Intelligent Interactive Multimedia Systems and Services 2016 - Pietro, Giuseppe De.; Gallo, Luigi; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book contains the contributions presented at the ninth international KES conference on Intelligent Interactive Multimedia: Systems and Services, which took place in Puerto de la Cruz, Tenerife, Spain, June 15-17, 2016. It contains 65 peer-reviewed book chapters that focus on issues ranging from intelligent image or video storage, retrieval, transmission and analysis to knowledge-based technologies, from advanced information technology architectures for video processing and transmission to advanced functionalities of information and knowledge-based services. We believe that this book will serve as a useful source of knowledge for both academia and industry, for all those faculty members, research scientists, scholars, Ph.D. students and practitioners, who are interested in fundamental and applied facets of intelligent interactive multimedia.
Analysis of Similarity Measurements in CBIR Using Clustered Tamura Features For Biomedical Images -- 2-Stripes Block-Circulant LDPC Codes for Single Bursts Correction -- Data Dictionary Extraction for Robust Emergency Detection -- SmartCARE - An ICT Platform in the Domain of Stroke Pathology To Manage Rehabilitation Treatment and Telemonitoring at Home -- Optimal Design of IPsec-based Mobile Virtual Private Networks for Secure Transfer of Multimedia Data -- Malicious Event Detecting in Twitter Communities -- Adopting Decision Tree Based Policy Enforcement Mechanism to Protect Reconfigurable Devices -- Arabic Named Entity Recognition: A Survey and Analysis -- Exploitation of Web Resources Towards Increased Conversions and Effectiveness -- How to Manage Keys and Reconfiguration in WSNs Exploiting SRAM Based PUFs -- Fast Salient Object Detection in Non-Stationary Video Sequences Based on Spatial Saliency Maps -- Global Motion Estimation Using Saliency Maps in Non-Stationary Videos with Static Scenes -- SVM-Based Cancer Grading from Histopathological Images using Morphological and Topological Features of Glands and Nuclei.-On Preservation of Video Data When Transmitting in Systems That Use Open Networks -- An invariant subcode of linear code -- Development Prospects of the Visual Data Compression Technologies and Advantages of New Approaches -- A Near-far Resistant Preambleless Blind Receiver with Eigenbeams Applicable to Sensor Networks -- A New Approach for Subsurface Wireless Sensor Networks -- Implementation of Mobile Sensing Platform with a Tree Based Sensor Network -- Prototype Implementation of Actuator Sensor Network for Agricultural Usages -- Development of Multi-Hop Field Sensor Networks with Arduino Board -- Communication Simulator with Network Behavior Logging Function for Supporting Network Construction Exercise for Beginners -- A New Method to Apply BRAKE to Sensor Networks Aiming At Power Saving -- A Tool for Visualization of Meteorological Data Studied for Integration in a Multi Risk Management System -- An Algorithm for Calculating Simple Evacuation Routes in Evacuation Guidance Systems -- SkyCube-tree Based Group-by Query Processing in OLAP Skyline Cubes.-Trends of Teaching/learning Issues through Analysis of Conference Presentation Articles.-Motion Prediction for Ship-Based Autonomous Air Vehicle Operations -- The Effect of Receding Horizon Pure Pursuit Control on Passenger Comfort in Autonomous Vehicles -- From Automotive to Autonomous: Time-Triggered Operating Systems -- Active Suspension Investigation Using Physical Networks -- Automatic Generation of Trajectory Data Warehouse Schemas -- A Taxonomy of Support Vector Machine for Event Streams Classification -- Social Networks Security Policies -- Recommending Multidimensional Spatial OLAP Queries.-Modeling Moving Regions: Colorectal Cancer Case Study -- A UML/MARTE Extension for Designing EnergyHarvesting in Wireless Sensor Networks -- A Survey on Web Service Mining Using QoS and Recommendation Based on Multidimensional Approach -- Mapping and Pocketing Techniques for Laser Marking of 2D Shapes on 3D Curved Surfaces -- 3DHOG for Geometric Similarity Measurement and Retrieval on Digital Cultural Heritage Archives -- Computer Aided Process as 3D Data Provider in Footwear Industry -- CoolTour: VR and AR Authoring Tool to Create Cultural Experiences -- Emotional Platform for Marketing Research -- Gamification as a Key Enabling Technology for Image Sensing and Tagging -- Bridging Heritage and Tourist UX - A Socially-driven Perspective -- A Personalised Recommender System for Tourists on City Trips: Concepts And Implementation -- Experience-Driven Framework for Technologically-enhanced Environments: Key Challenges and Potential Solutions -- Touchless Disambiguation Techniques for Wearable Augmented Reality Systems -- System Architecture and Functions of Internet-Based Production of Tailor-Made Clothes -- Influence of some Parameters on Visiting Style Classification in a Cultural Heritage Case Study -- Opinions Analysis in Social Networks for Cultural Heritage Applications -- A Forward-Selection Algorithm for SVM-Based Question Classification in Cognitive Systems -- Supporting Autonomy in Agent Oriented Methodologies -- A Data-driven Approach to Dynamically Learn Focused Lexicons for Recognizing Emotions in Social Network Streams -- Disaster Prevention Virtual Advisors Through Soft Sensor Paradigm -- A Personal Intelligent Coach for Smart Embodied Learning Environments -- A model of Social Chatbot -- An Experience of Engineering of MAS for Smart Environments: Extension of ASPECS -- A Norm-based Approach for Personalising Smart Environments -- Adopting a Middleware for Self-Adaptation in the Development of a Smart Travel System -- Pentas: Using satellites for Smart Sensing -- A Multiple Data Stream Management Framework for Ambient Assisted Living Emulation -- Soft Sensor Network for Environmental Monitoring -- The Use of Eye Tracking (ET) in Targeting Sports: a review of the Studies on Quiet Eye (QE) -- The Elapsed Time During a Virtual reality Treatment for Stressful Procedures. A Pool Analysis on Breast Cancer Patients During Chemotherapy.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence